Children and Cinema: Moving Images of Childhood - Bushati, Angela (European Journal of Multidisciplinary Studies, 2018)
The idea of childhood has been part of the moving images experience since the appearance of cinema. Through the lenses of cinema, childhood is deconstructed as presenting branching pathways, underlining its complexity and the mysteriousness of it. The ongoing experience of childhood on screen serves as a tool to reflect on the anatomy and contour of cinema, as well as its understanding. On the other hand, cinema has been used as a tool to reflect on the notion of childhood and as an apparatus that challenges the power relations that exist between adults and children. The aim of this paper is to present an overview of how the institution of cinema contributes or opposes the notion of naturalness of childhood imposed by adults or the normative perception of what a child should be. In a lot of movies the child is “othered” leaving as a result an ambiguous space between the child and cinema, where childhood is not anymore strictly defined.